Individualized home-based exercise and nutrition interventions improve frailty in older adults: a randomized controlled trial - Tsung-Jen Hsieh; Shin-Chang Su; Chun-Wei Chen; Yaw-Wen Kang; Ming-Hsia Hu; Li-Lin Hsu; Szu-Yun Wu; Likwang Chen; Hsing-Yi Chang; Shao-Yuan Chuang; Wen-Harn Pan; Chih-Cheng Hsu (BMC, 2019)
Abstract Background Frail older adults are predisposed to multiple comorbidities and adverse events. Recent interventional studies have shown that frailty can be improved and managed. In this study, effective individualized home-based exercise and nutrition interventions were developed for reducing frailty in older adults. Methods This study was a four-arm, single-blind, randomized controlled trial conducted between October 2015 and June 2017 at Miaoli General Hospital in Taiwan. Overall, 319 pre-frail or frail older adults were randomly assigned into one of the four study groups (control, exercise, nutrition, and exercise plus nutrition [combination]) and followed up during a 3-month intervention period and 3-month self-maintenance period. Improvement in frailty scores was the primary outcome. Secondary outcomes included improvements in physical performance and mental health. The measurements were performed at baseline, 1 month, 3 months, and 6 months. Results At the 6-month measurement, the exercise (difference in frailty score change from baseline: − 0.23; 95% confidence interval [CI]: − 0.41, − 0.05; p = 0.012), nutrition (− 0.28; 95% CI: − 0.46, − 0.11; p = 0.002), and combination (− 0.34; 95% CI: − 0.52, − 0.16; p <  0.001) groups exhibited significantly greater improvements in the frailty scores than the control group. Significant improvements were also observed in several physical performance parameters in the exercise, nutrition, and combination groups, as well as in the 12-Item Short Form Health Survey mental component summary score for the nutrition group. Conclusions The designated home-based exercise and nutrition interventions can help pre-frail or frail older adults to improve their frailty score and physical performance. Trial registration Retrospectively registered at ClinicalTrials.gov (identifier: NCT03477097); registration date: March 26, 2018.